In-situ monitoring the effect of acoustic vibration in the form of music on the motility of Escherichia coli. (15th January 2021) - Ku, Hsin-Ning; Lin, Wei-Feng; Peng, Hwei-Ling; Yew, Tri-Rung
Graphical abstract: Highlights: New approach of in-situ monitoring the musical effect on the motility of E. coli . Music with higher frequency and faster tempoenhanced the motility of E. coli . The improvement of motility was quantified by indirect and direct monitoring assay. Abstract: In this work, a new analytical approach combining optical microscope with software was carried out to study the effect of music on bacteria and to explore its potential mechanism. The stimulation of classical music (Flight of the Bumblebee) with different frequencies (range from 55 Hz to 4186 Hz) and tempos (range from 25 BPM to 250 BPM) was transmitted in the form of vibration by the apparatus which was bone conduction to Escherichia coli MG1655. The increment of E. coli motility affected by Flight of the Bumblebee was quantified by two approaches. One was indirect motility assay and the other was the in-situ monitoring on the swimming behavior of E. coli under the optical microscope. The in-situ monitoring was conducted by combining optical microscope with software which enabled real-time observation on the swimming behavior of E. coli. Both results showed that different frequencies and tempos of musical vibration affected the motility to a different extent. With comparison, it was found that the music with higher frequency and faster tempo could enhance more on the motility . Above findings suggest this new analytical approach could be applied for investigating the motility of E. coli, and also a potential mechanism to modulate biological cells for future digital therapeutic and medical device applications.